L’Affaire Redureau, le crime de Bas-Briacé (1913) : Un meurtrier de 15 ans au cœur des complaintes - Sophie Victorien; Pierre Guillard (Criminocorpus)
The Redureau Affair depicts a 15-year-old criminal who executed his winegrowing boss in Brittany and 6 other members of the family on the night of 30 September 1913. The purpose of our subject is to evoke, through the laments, the horror caused by this extremely violent crime perpetrated by a young boy who was hitherto without history and the persistence of the fascination that this affair can exert. It is also a question of comparing the message conveyed by the press and the complaints with the contempt sometimes shown for the reality of the facts and the legislation. This persistence of the memory of the horror caused by this gesture is further developed by Pierre Guillard, who draws on the most well-known lament concerning this affair, discovered during a work of harvesting and co-collecting songs from oral traditions undertaken in the late 1980s and early 1990s.